(untitled) - Johnson, Diane (New York, 2003)
Traveling to Europe to learn about her culture and find investment opportunities, successful dot-com executive Amy Hawkins becomes involved in an estate dispute involving the numerous children--many illegitimate--of an avalanche victim.
Keywords: English language,Ngôn ngữ Anh; Study and teaching,Học và dạy